Controllable Construction of Bifunctional CoxP@N, P‐Doped Carbon Electrocatalysts for Rechargeable Zinc–Air Batteries. Issue 2 (15th June 2021) - Shi, Qing; Liu, Qiao; Zheng, Yapeng; Dong, Yaqian; Wang, Lin; Liu, Hantao; Yang, Weiyou
Abstract : The exploration of cheap, efficient, and durable bifunctional electrocatalysts for oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) is highly desired to push forward the commercialization of rechargeable metal–air batteries. Here, bifunctional ORR/OER electrocatalysts based on Co x P (0 <  x  < 2, i.e., Co2 P, Co2 P/CoP mixture, and CoP) nanoparticles (NPs) anchored on N, P‐doped carbon framework (Co x P@NPC) are developed via one‐step carbonization of the mixture of as‐synthesized ZIF‐67 and melamine–phytic acid supermolecular aggregate (MPSA). The stoichiometric ratio of resultant Co x P NPs can be rationally designed by adjusting the introduced ratio of ZIF‐67 to MPSA, enabling their fabrication in a controlled manner. It is found that the as‐synthesized Co2 P@NPC exhibits the best bifunctional ORR/OER activity among the Co x P@NPC analogues, with a reversible oxygen electrode index (Δ E  =  E j10  −  E 1/2 ) down to ~0.75 V. The constructed Zn–air battery based on Co2 P@NPC delivers a peak power density of 157 mW cm −2 and an excellent charge‐discharge stability with negligible voltage decay for 140 h at 10 mA cm −2, superior to those based on Pt/C+RuO2 and most Co x P‐based electrodes ever reported. Abstract : Controllable construction of Co x P (0 <  x  < 2) nanoparticles anchored on N, P‐doped carbon frameworks is reported for efficient and durable oxygen reduction reaction and oxygen evolution reaction.